Cross-Sectoral Integration Strategy for Madrasah Electronic Diplomas to Accelerate Digital Transformation and Educational Accountability - Nurham (JURNAL ILMIAH GEMA PERENCANA, 2026)
National digital transformation demands accurate and accountable educational data integration; however, the implementation of electronic diplomas in madrasahs faces serious obstacles due to the inability of cross-sectoral system interoperability. The central issue of this study focuses on the prevalence of sectoral ego and inter-institutional policy fragmentation, leading to weak binding regulations for data interconnection. This study employs a descriptive-analytical approach with a policy analysis methodology encompassing problem prioritization using the USG (Urgency, Seriousness, Growth) method and policy alternative evaluation based on William N. Dunn’s criteria. The results indicate that the absence of homogeneous data exchange protocol (API) standards and low data integrity at the input level are the primary factors undermining digital educational accountability. Discussions based on Digital Silos and Collaborative Governance theories reveal that without collective commitment, madrasah electronic diplomas will remain isolated from the national digital ecosystem. The conclusion emphasizes that technical solutions must be accompanied by a bureaucratic paradigm shift from a silo-based model to a connected government. Therefore, it is recommended that the Minister of Religious Affairs immediately initiate the formation of a Joint Ministerial Decree (SKB) to establish binding interoperability standards and certified digital document legality recognition to guarantee graduates' digital rights and support the Indonesia Digital 2045 vision.